Insectos asociados al cultivo de tempate (Jatropha curcas) en el Pacifico de Nicaragua. III. Coreoidea (Heteroptera) - Grimm, C.=700 1 Maes, J.M.
(Es, En)
Ilus., 14 ref.
Keywords: COREIDAE; RHOPALIDAE; HETEROPTERA; INSECTOS CHUPADORES; PLAGAS; CULTIVO; JATROPHA CURCAS; NICARAGUA; ALYDIDAE; REVISTA NICARAGUENSE DE ENTOMOLOGIA